Gender representation and visibility of women in top-rated Netflix original films: A 2025 streaming media analysis - Syeda Zehra; Maha E. Darakshan; Syeda M. Begum (AFRICAN JOURNAL OF REPRODUCTIVE HEALTH, 2026)
This research examines numerical data that reflects gender gap and underrepresentation of women in top-rated Netflix Originals during 1st January to 1st December, 2025 to find out if Netflix follows Diversity, Equity and Inclusion (DEI) pledges in its original content. We conducted mixed-method analysis on the 4 shortlisted films with 7.5 or above IMDb ratings, and used quantitative content analysis approach to find gender disparity and qualitative content analysis approach (Bechdel Test) to evaluate women’s representation in films. The study found that men dominate as lead actors, writers, directors and producers, 75% of the films have a male-driven story, and 3 out of 4 films do not pass the Bechdel Test. The findings indicate imbalance within the selected high-rated sample. The research argues that the relation between streaming platforms and diverse content is more complex than they present in their discourse and aims to contribute to the discussion around this imbalance by encouraging critical thinking.